Facility Degradation in Surabaya Zoo - Oktavia, Rani; Larasati, Diyas Age; Azhara, Andita Amma; Ningrum, Dwi Agus Tina; Saputra, Maulana Rafi Rulis; Sodik, Fajar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The zoo is one of the popular educational tourist destinations in Surabaya. Issues regarding facilities, service quality and animal welfare are always the subject of evaluation because they are to satisfy visitors to the Surabaya Zoo. This study used direct observation methods, unstructured interviews and documentation at the Surabaya Zoo. The results of the study showed that the destruction of facilities at the Surabaya Zoo is a common occurrence and a serious problem that can disrupt the comfort of visitors and animal welfare. This study discusses the behavior of visitors who can damage facilities at the Surabaya Zoo and the lack of supervision from the Surabaya Zoo. This study is expected to encourage the authorities at the Surabaya Zoo to take steps to improve and revitalize the Surabaya Zoo, for the sake of sustainable conservation and to become a better educational environment and can provide a good impression for visitors to the Surabaya Zoo in the future.